A new intronic quantitative PCR method led to the discovery of transformation from human ascites to murine malignancy in a mouse model - Jin, Jiankang; Huo, Longfei; Fan, Yibo; Wang, Ruiping; Scott, Ailing W.; Pizzi, Melissa Pool; Yao, Xiaodan; Shao, Shan; Ma, Lang; Da Silva, Matheus S.; Yamashita, Kohei; Yoshimura, Katsuhiro; et al. (Frontiers in Oncology, 2023)
Purpose: To establish a fast and accurate detection method for interspecies contaminations in patient-derived xenograft (PDX) models and cell lines, and to elucidate possible mechanisms if interspecies oncogenic transformation is detected. Methods: A fast and highly sensitive intronic qPCR method detecting Gapdh intonic genomic copies was developed to quantify if cells were human or murine or a mixture. By this method, we documented that murine stromal cells were abundant in the PDXs, we also authenticated our cell lines to be human or murine. Results: In one mouse model, GA0825-PDX transformed murine stromal cells into a malignant tumorigenic murine P0825 cell line. We traced the timeline of this transformation and discovered three subpopulations descended from the same GA0825-PDX model: epithelium-like human H0825, fibroblast-like murine M0825, and main passaged murine P0825 displayed differences in tumorigenic capability in vivo. P0825 was the most aggressive and H0825 was weakly tumorigenic. Immunofluorescence (IF) staining revealed that P0825 cells highly expressed several oncogenic and cancer stem cell markers. Whole exosome sequencing (WES) analysis revealed that TP53 mutation in the human ascites IP116-generated GA0825-PDX may have played a role in the human-to-murine oncogenic transformation. Conclusion: This intronic qPCR is able to quantify human/mouse genomic copies with high sensitivity and within a time frame of a few hours. We are the first to use intronic genomic qPCR for authentication and quantification of biosamples. Human ascites transformed murine stroma into malignancy in a PDX model.